Influence of In-Ovo ATP Injection on Hatching Performance, Morphometry, and Carcass Traits in Sentul Chickens under Moderate-Latitude Conditions - Shiddiq, Muhammad Rasyid; Ulfah, Maria; Anggraini, Lili; Krisnan, Rantan (Faculty of Animal Science, Universitas Brawijaya, 2026)
In this study, the effects of in ovo injection with adenosine triphosphate (ATP) on the hatching performance, body measurements, and carcass characteristics of Sentul chickens, an indigenous breed of Indonesia, were evaluated. ATP, a key nucleotide that mediates cellular energy transfer, was injected into the amniotic cavity on day 18 of incubation. Unsex 250-day-old chicks (DOCs) were subjected to two treatments: control (P1: without ATP injection) and ATP injection on the 18th day of incubation (P2). The birds were maintained in three replicates per treatment, and the cage was considered the experimental unit. During the rearing period, the birds were redistributed according to three growth stages: period I (1–14 days, 2 cages, 125 chicks per cage), period II (15–28 days, 6 cages, 30 birds per cage), and period III (29–56, 12 cages, 15 birds per cage). The data were analysed using an independent t test, and differences were considered significant at P<0.05. ATP injection slightly improved hatchability (92,8 ± 0,71) and hatching weight (33,12 ± 0,56) compared with those of the control group (91,2 ± 0,93 and 32,50 ± 0,66, respectively), although the differences were not statistically significant (p>0,05). However, compared with the control treatment, the ATP treatment significantly improved several morphometric traits, including tibia length in Period I (4,60 ± 0,40 vs, 3,78 ± 0,70; P<0.05) and wing and chest lengths across the observation periods (p<0.05). At 8 weeks of age, compared with the control group (404.50 ± 196.49 g; P < 0.05), the group receiving ATP injection had a higher carcass weight (474.58 ± 206.22 g), whereas the carcass percentage and the meat-to-bone ratio were not significantly affected (P > 0.05). These findings indicate that in ovo ATP injection may increase the skeletal growth and carcass weight of Sentul chickens without affecting hatchability or carcass composition.